Slaughter qualities of young sheep depending on genotype - Yusupzhan A. Yuldashbaev; Vladimir I. Kosilov; Elena A. Nikonova; Tatyana A. Sedykh; Olga A. Bykova (RUDN Journal of Agronomy and Animal Industries)
Influence of the effect of crossing the Romanov and Edilbay sheep breeds on the main indicators of slaughter was studied. As the object of study, we used the Romanov breed (I group), its crosses with the Edilbay breed of the first generation ( Romanov Edilbay - II group) and the second generation ( Romanov Edilbay - III group). The effect of crossing in terms of slaughter qualities in crossbred young animals was established. At the same time, wethers of group I were inferior to crossbred peers of groups II and III in terms of the carcass fullness coefficient K 1 by 3.40 and 4.48 %, respectively, and the level of thigh completion coefficient - by 6.80 and 7.82 %, respectively. Crossbreeds of groups II and III were superior to purebred wethers of group I in pre-slaughter live weight by 11.18 kg and 13.32 kg, fresh carcass weight - by 6.03 kg and 7.56 kg, carcass yield - by 1.63 and 2.62 %, slaughter weight - by 6.16 kg and 8.00 kg, slaughter yield - by 1.57 and 2.71 %, respectively. The advantage in terms of the studied slaughter indicators was in the second generation crossbreeds of the third experimental group.